Career perspectives of BA German graduates in Malaysia: a case study of the 2009-2011 graduates from Universiti Putra Malaysia - Schaar, Torsten (International Organization Of Scientific Research, 2016)
Since its introduction in 2001, 164 Malaysian undergraduates have completed the BA German programme at Universiti Putra Malaysia (UPM), a combination of German language instruction, philological subjects and market-oriented courses. A survey into the professional development of BA German students since their graduation revealed that the majority of graduates had no problems in finding employment in the corporate or education sector shortly after finishing their studies. Many have changed their career paths several times since securing their first employment in order to gain higher incomes, face greater challenges and enjoy better career opportunities. Some graduates became teachers of German or other languages (Malay language, English, and Mandarin) as well as for science subjects at primary and residential schools, colleges and universities. Furthermore, several opted for Master’s degrees and PhD’s. A tracer study project aimed to provide comprehensive data on the professional and personal development of BA German graduates from UPM. The 2009, 2010 and 2011 graduates were chosen to provide data via in-depth interviews, questionnaires and social media groups, which allowed the conclusion that studying BA German at UPM combined with a business-related minor subject is a proven formula for a successful and quick entry into the Malaysian job market.